2016
DOI: 10.4269/ajtmh.15-0784
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality of Care of Community Health Worker and Facility-Based Health Worker Management of Pneumonia in Children Under 5 Years in Western Kenya: A Cross-Sectional Multidimensional Study

Abstract: Abstract. Integrated community case management (iCCM) programs that train lay community health workers (CHWs) in the diagnosis and treatment of diarrhea, malaria, and pneumonia have been increasingly adopted throughout subSaharan Africa to provide services in areas where accessibility to formal public sector health services is low. One important aspect of successful iCCM programs is the acceptability and utilization of services provided by CHWs. To understand community perceptions of the quality of care in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…Their top-ranked research objective was to “assess perceptions of beneficiaries and levels of community satisfaction in community health workers’ capacity.” Since then, one other study, also in Uganda, has assessed community usage and perspectives on iCCM services, reporting that 53% of those who had received iCCM services were satisfied with care [ 2 ]. Other studies have examined satisfaction with home-based fever or pneumonia management alone rather than iCCM; one study in Ghana demonstrates that a majority of caregivers rated home-based management of fever by a VHW as “good” or “excellent” [ 3 ], while another study in Kenya describes caregivers’ expressed preference for home-based pneumonia care over facility-based care [ 4 ]. By comparison, a study in Pakistan of home-based pneumonia and diarrhoea care described very low use of and confidence in community health workers to provide care for these conditions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their top-ranked research objective was to “assess perceptions of beneficiaries and levels of community satisfaction in community health workers’ capacity.” Since then, one other study, also in Uganda, has assessed community usage and perspectives on iCCM services, reporting that 53% of those who had received iCCM services were satisfied with care [ 2 ]. Other studies have examined satisfaction with home-based fever or pneumonia management alone rather than iCCM; one study in Ghana demonstrates that a majority of caregivers rated home-based management of fever by a VHW as “good” or “excellent” [ 3 ], while another study in Kenya describes caregivers’ expressed preference for home-based pneumonia care over facility-based care [ 4 ]. By comparison, a study in Pakistan of home-based pneumonia and diarrhoea care described very low use of and confidence in community health workers to provide care for these conditions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A mixed methods approach allowing triangulation of qualitative and quantitative findings would have provided a deeper understanding of the drivers of health seeking preferences, satisfaction and perceived quality of the services. While we did not conduct qualitative work, a substudy within the parent project compared the perceived quality of services and health seeking behaviors among those seeking care from CHWs versus health facilities[19]. This substudy found that caregivers perceived CHWs to provide higher quality care in terms of accessibility and patient relationship and equal quality care in terms of clinical aspects[19].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not conduct qualitative work, a substudy within the parent project compared the perceived quality of services and health seeking behaviors among those seeking care from CHWs versus health facilities[19]. This substudy found that caregivers perceived CHWs to provide higher quality care in terms of accessibility and patient relationship and equal quality care in terms of clinical aspects[19]. Our results are therefore complimentary to this previous study and support that notion that iCCM for pneumonia is cost-effective and acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve the quality of child health services, the World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) developed the Integrated Community Case Management (iCCM) of childhood illnesses strategy [7]. This strategy aims to reduce morbidity and mortality among children under the age of 5 years through improved health workers' skills by training and supportive supervision; improved health systems, including equipment, supplies, organization of work and referral systems; and improved key family practices and child care at community and household levels [8].…”
Section: Introductionmentioning
confidence: 99%